Influência da suplementação com frutose e ômega-3 em um modelo de enxaqueca induzido por nitroglicerina em ratos : mecanismos associados - Barbosa, Isadora Randon (2022)
Migraine is among the most disabling disorders in the world. The current available treatments have unsatisfactory efficacy as well as undesirable side effects. Literature data points out an association between migraine and metabolic syndrome (MS). This correlation is not well understood, but there is evidence that some components of MS are involved in the pathogenesis of migraine, such as leptin, adiponectin and pro-inflammatory cytokines. Alternatively, there is evidence suggesting that metabolic dysfunctions might coexist with migraine, developing as an adaptive mechanism to protect the central nervous system that demands greater amounts of energy, while lacking energy efficiency and oxidative stress control. The polyunsaturated fatty acid omega-3 (n-3) has anti-inflammatory properties and clear beneficial effects on metabolism, making it a promising supplement in the prevention of migraine and metabolic disorders, considering its mechanisms of action. The present study aimed to investigate the effects of high-fructose diet (HFD) and n-3 supplementation in a nitroglycerin (NTG)-induced rat migraine model, considering the behavioral, inflammatory and metabolic perspectives. In the first study, HFD decreased the painful symptoms of NTG-induced migraine, as indicated by decreased Grimace nociception scores, paralleled by reduced serum levels of calcitonin gene-related peptide (CGRP) and leptin, increased hypothalamic CGRP, and decreased hypothalamic adiponectin and interleukin-6 (IL-6). In addition, there was a recovery of body weight and adipose tissue, as well as a reduction of crown like structures (CLS) in the inguinal adipose tissue of HFD NTG-injected rats. N-3 supplementation had no effect on NTG-related pain. Otherwise, n-3 reduced the body weight and adipose tissue of NTG-injected rats, either those that received HFD or tap water. Nevertheless, n-3 supplementation improved the affective behavior related to HFD and NTG injections, as well as the inflammatory parameters of tap water NTG-injected rats, evidenced by the decrease in the hypothalamic tumor necrosis factor (TNF), serum CGRP and inguinal adipose CLS. In the second part of the study, tap water NTG-injected rats showed increased glucose metabolism in the hypothalamus (HT) and insular cortex (ICo), decreased glucose metabolism in the visual cortex (VC), as well as a slight increase in the expression of cortical peroxisome proliferator-activated gamma receptor (PGC-1α). HFD NTG-injected rats showed increased glucose metabolism in the superior and inferior colliculus (SC and IC, respectively), along with a greater activation of glial satellite cells (SGC) in the trigeminal ganglion (TG), besides augmented inosine levels. Collectively, the data indicate an alleviation of migraine in the presence of HFD, possibly due to reduced caloric expenditure, thus minimizing energy requirements. Furthermore, HFD might increase glucose uptake in key brain regions involved in migraine, stimulating SGC activation in the TG, as well as regulating purine metabolism and mitochondrial biogenesis default in NTG-injected rats. These modifications can be associated with an overall improvement in face of the deleterious effects of NTG-induced migraine. Conversely, n-3 showed favorable effects only in relation to the affective behavior and central and peripheral inflammation, regardless of HFD. The present findings reveal some key mechanisms and open new avenues towards the discovery of treatments to improve bioenergetics in migraine, bringing more effective alternatives for managing migraine.